Real time cable force identification by short time sparse time domain algorithm with half wave. (February 2020) - Xue, Songling; Shen, Ruili
Abstract: In the fatigue damage analysis of cables, it is very important to understand the cable force history. However, most current cable force identification methods are based on the average cable force assumption. To overcome this issue, this paper proposes the short time sparse time domain algorithm combined with the simplified half wave method (STSTD + SHW). This method only requires one acceleration sensor and is thus simple, economical, convenient, and fast. Its reliability and accuracy were verified by two experiments and one engineering application. According to the results, this method does not only reduce the influence of the boundary conditions on cable force identification but can also quickly identify the dynamic cable force. Moreover, only one accelerometer is required to avoid the problem of sensor placement and optimization, which is conducive to practical engineering applications.